Hb Levels in Pregnant Women with Consumption of Sweet Potatoes (Ipomoea Batatas L): History of Malaria - Ika Wijayanti; Eyllonggia Mawene (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Anemia in pregnancy is defined as a condition when the mother has a hemoglobin level of 7-10.5 g%. Handling of anemia can be done in a non-pharmacological way. namely with herbal or plant medicines, such as red spinach, green beans, beta vulgaris L fruit (beets), and dates and sweet potatoes. in 100 grams of sweet potato contains 4 mg of iron which can increase hemoglobin levels in red blood cells. The purpose of this study was to determine the effect of consumption of sweet potato (Ipomoea batatas L) on increasing hemoglobin levels in pregnant women with a history of malaria in the working area of Abepantai Public Health Center. The research method used a quasi-experimental research design with Pretest-Postest Design with Control Group. Sampling technique with total sampling. The sample in this study were pregnant women in the third trimester with anemia. intervention with sweet potato consumption for 7 days. with hemoglobin examination before and after the intervention. There is an effect of consumption of sweet potato (Ipomoea batatas L) on the increase in hemoglobin levels in pregnant women in the working area of Abepantai Health Center. It is hoped that the consumption of sweet potatoes can help increase hemoglobin in pregnant women with anemia.